2023
DOI: 10.1002/biot.202300301
|View full text |Cite
|
Sign up to set email alerts
|

Influence of biosynthesized magnesium oxide nanoparticles on growth and physiological aspects of cowpea (Vigna unguiculata L.) plant, cowpea beetle, and cytotoxicity

Nilly A. H. Abdelfattah,
Manar Ali Yousef,
Ali A. Badawy
et al.

Abstract: Recently, agricultural management innovation has incorporated engineered nanoparticles. The current investigation was carried out to produce magnesium oxide nanoparticles (MgONPs) for the first time applying S. cerevisiae extract. FTIR, XRD), HRTEM, and zeta potential analysis were used to characterize the MgONPs. The FTIR data show that the bioactive substances reduce and cap the synthesized MgONPs. The crystalline metallic MgONPs had four significant peaks in the XRD pattern. The size and form of MgONPs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…In this regard, the nano-Hap variant displayed the lowest population of terrestrial insects while concurrently maintaining relatively higher sunflower yields and yield-related parameters. This outcome aligns with findings observed with MgO-NPs and cowpea (Vigna unguiculata L.) [3]. In this context, NPs have the potential to penetrate an insect's circulatory system, inducing toxic effects on the lymphatic systems, ultimately leading to the generation of oxidative stress and mortality [76].…”
Section: Evaluation Of Terrestrial Insect Diversity Following Applica...supporting
confidence: 84%
See 1 more Smart Citation
“…In this regard, the nano-Hap variant displayed the lowest population of terrestrial insects while concurrently maintaining relatively higher sunflower yields and yield-related parameters. This outcome aligns with findings observed with MgO-NPs and cowpea (Vigna unguiculata L.) [3]. In this context, NPs have the potential to penetrate an insect's circulatory system, inducing toxic effects on the lymphatic systems, ultimately leading to the generation of oxidative stress and mortality [76].…”
Section: Evaluation Of Terrestrial Insect Diversity Following Applica...supporting
confidence: 84%
“…The primary objective in NF development is the reduction in traditional fertilizers to nanoscale dimensions [1]. Applied NFs follow a definition similar to that of nanomaterials (NMs), where one of the three dimensions should not exceed 100 nm; otherwise, it becomes a mixture of NF with micro-sized fertilizers [2][3][4]. Significantly, the size of nanoparticles (NPs) in NFs, compared to their analogical chemical macro-sized or ionic counterparts, implicates different reactivity, mobility, and bioavailability [5].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, Cd stress significantly decreased the SPAD value and photosynthetic pigment content of ramie leaves, and the external application of Xh could alleviate these Cd-induced changes (Figure 2a-c). Carotenoids are not only photosynthetic pigments but also endogenous antioxidants with an important role in ROS scavenging [32,33]. We observed that the Cd-induced decreases in MDA, H 2 O 2 , and proline levels in ramie were attenuated by the addition of Xh (Figure 3).…”
Section: Discussionmentioning
confidence: 83%
“…Differently, magnesium (Mg) increased following LE treatments, and this aligns with what has been found for chlorophyll a and total chlorophyll. Mg is an essential element for plant nutrition and development, and it is necessary for plant growth and productivity, being part of chlorophyll and playing a central role in photosynthesis [62]. The other elements investigated, iron (Fe), manganese (Mn), and zinc (Zn), are essential micronutrients involved in numerous biological processes.…”
Section: Discussionmentioning
confidence: 99%